Scratch and Computational Thinking in Elementary School: A Meta-analysis - Maulana Malik Ibrohim; Eveline Siregar; Uwes Anis Chaeruman (AL-ISHLAH: Jurnal Pendidikan, 2023)
Computational thinking has become a fundamental skill that all students must possess. Learning to program with Scratch is considered the most effective way to improve students’ computational thinking skills. Many studies prove its effectiveness in learning in elementary schools. However, no study discusses the systematic aggregation of the results of these studies, especially in the context of learning programming in elementary schools. Therefore, this meta-analysis aims to calculate the cumulative effect of twenty-two data sets obtained from fourteen relevant quantitative research results. The data collection procedure was carried out using PRISMA and analyzed using the JASP statistical test software. The calculation of effect size shows that the use of Scratch has significant effects on the computational thinking skills of elementary school students, both as a whole and in each of its dimensions. The dimensions of computational thinking skills that are most affected are computational concepts and practices. Differences also influence these skills in student age, where students aged 9-12 years are most affected by the use of Scratch in learning. However, it was not found that there was a significant effect of differences in the duration of learning programming using Scratch on computational thinking skills in all dimensions.